No Association of Plantar Aponeurosis Stiffness with Medial Longitudinal Arch Stiffness - Noro, Hiroaki; Miyamoto, Naokazu; Mitsukawa, Naotoshi; Yanagiya, Toshio (International Journal of Sports Medicine, 2021)
Lower stiffness of the medial longitudinal arch is reportedly a risk factor for lower leg disorders. The plantar aponeurosis is considered essential to maintaining the medial longitudinal arch. It is therefore expected that medial longitudinal arch stiffness is influenced by plantar aponeurosis stiffness. However, this has not been experimentally demonstrated. We examined the relationship between the plantar aponeurosis stiffness and medial longitudinal arch stiffness in humans in vivo. Thirty young subjects participated in this study. The navicular height and shear wave velocity (an index of stiffness) of the plantar aponeurosis were measured in supine and single-leg standing positions, using B-mode ultrasonography and shear wave elastography, respectively. The medial longitudinal arch stiffness was calculated based on body weight, foot length, and the difference in navicular height between the supine and single-leg standing conditions (i. e., navicular drop). Shear wave velocity of the plantar aponeurosis in the supine and single-leg standing positions was not significantly correlated to medial longitudinal arch stiffness (spine: r=−0.14, P=0.45 standing: r=−0.16, P=0.41). The findings suggest that the medial longitudinal arch stiffness would be strongly influenced by the stiffness of foot structures other than the plantar aponeurosis.
Keywords: plantar fasciitis; shear wave elastography; ultrasonography; plantar fascia